Pulex irritans on Dogs and Cats: Morphological and Molecular Approach - Amrollah Azarm; Abdolhossin Dalimi; Majied Pirestani; Anita Mohammadiha; Alireza Zahraei-Ramazani; Narges Marvi-Moghaddam; Esmaiel Amiri (Journal of Arthropod-Borne Diseases, 2023)
Background: The painful bite of Pulex irritans; causes wound on the host body and is a vector for Bartonella bacteria species, which can cause trench fever, Rickettsia species, Rocky Mountain spotted fever and Mediterranean spotted fever. We conducted a study to find out the hosts, abundance, as well as the molecular characteristics of this flea species in Meshkin-Shahr county, Ardabil province, northwest of Iran.